Teaching with Humor: Reflections on Its Relevance in Pedagogical Practice - Abílio Lourenço; Sergio Dominguez-Lara; Sabina Valente (Journal of Advanced Research in Education, 2025)
This study focuses on an affective dimension of pedagogical practices in the classroom—humor—to foster more human and emotional interactions. Through a literature review, it reflects on how humor can be an effective tool in teaching and learning, helping to create more positive environments conducive to educational development. This knowledge is valuable for structuring initial teacher training programs, and equipping educators to integrate humor intentionally and strategically. Humor, as a form of social interaction, is important in fostering closer interpersonal relationships and creating a positive classroom climate. Teaching with humor can strengthen these relationships, facilitate student learning, and significantly contribute to academic success. Additionally, the intentional use of humor aligns with the principles of educational sustainability, fostering a more inclusive, emotionally balanced, and collaborative learning environment that promotes the well-being of both students and teachers. The creation of sustainable educational spaces, grounded in trust, respect, and empathy, has a direct impact on building more cohesive and resilient communities. The conclusions highlight the need for teachers to consider humor as a pedagogical tool that can reduce interpersonal barriers and foster an environment of trust, respect, and collaboration. In this context, initial teacher training assumes a strategic role in providing educators with the necessary skills to apply humor in teaching effectively. Thus, it is emphasized that humor not only enhances the teaching and learning process but also plays a crucial role in building a more emotionally balanced, cooperative, and self-regulated society. Therefore, humor is presented as a crucial element in promoting sustainable pedagogical practices, contributing to the strengthening of social and emotional values essential for sustainable development.